A single center report of MScanFit motor unit number estimation in five muscles of healthy subjects - Song, Xiaohui; Cui, Lijun; Zong, Ya; Chen, Maoqi; Lu, Zhiyuan; Xie, Qing; Zhou, Ping (Frontiers in Human Neuroscience, 2023)
The objective of this study was to estimate the number of motor units in 5 muscles from healthy individuals using the MScanFit program based on compound muscle action potential (CMAP) scan recordings. The examined muscles included first dorsal interosseous (FDI), abductor pollicis brevis (APB), abductor digiti minimi (ADM), second lumbrical (SL), and abductor hallucis (AH). CMAP scans were recorded from a total of 24 healthy participants. Motor unit number estimation (MUNE) values were derived from the MScanFit program. The average MUNE was 136.1 ± 31.1 (mean ± standard deviation) for the FDI, 134.9 ± 37.4 for the APB, 127.3 ± 32.3 for the ADM, 39.6 ± 8.3 for the SL, and 143.9 ± 28.9 for the AH muscles. Findings of the study provide useful information of the MScanFit MUNE for the examined muscles of healthy subjects from a single center.